PUBLIC SECTOR EFFICIENCY IN INDONESIA (FISCAL DECENTRALIZATION ERA, 2001 â2008 - Kirana, Mayanggita; Saleh, Samsubar (Journal of Indonesian Economy and Business, 2011)
While many developing countries have devolved public responsibilities to localÂ governments in recent years, some studies have examined whether decentralizationactually leads to greater public sector allocation efficiency. This paper approaches thisÂ question by assessing the efficiency of government expenditure on public sector underfiscal decentralization. The area of public expenditure is of great importance making theÂ findings have strong implications with regard to public sector efficiency.We compute public sector performance (PSP) and public sector efficiency (PSE)Â indicators, comprising of composite and 9 sub indicators, for 33 provinces in Indonesia.The first 6 sub indicators are opportunity indicators that take into account education,Â health outcomes, poverty, gender equality, quality of public infrastructure (transportationand energy). 3 order indicators reflect the standard musgravian tasks for the government:Â allocation, distribution, and stabilization. The input and output efficiency of public sectorsÂ across provinces is then measured using a non-parametric production frontier technique.Free Disposable Hull (FDH) analysis is used to estimate the extent of slack in governmentÂ expenditures. The study finds significant differences in PSP and PSE, which suggests alarge potential for expenditure savings in many provinces. All these findings suggestÂ diminishing marginal products of higher public spending.We also estimate a semi parametric model of the public sector production process byÂ regressing FDH analysis output scores on non discretionary variables using the TobitÂ procedure. We show that inefficiency is strongly related to GDP per capita, humanÂ development index, and degree of fiscal dependence. The central message of this paper isÂ that increasing budgetary allocations for public sector may not be the only or mostÂ effective way to increase public sector outcome, and that more attention should be given toÂ increasing the efficiency of expenditure.Keywords: fiscal decentralization public sector performance, public sector efficiency,Â free disposable hull, Tobit